PiRNAs Warrant Investigation in Rett Syndrome: An Omics Perspective. Issue 5 (21st May 2013) - Saxena, Alka; Tang, Dave; Carninci, Piero
Abstract : Mutations in the MECP2 gene are found in a large proportion of girls with Rett Syndrome. Despite extensive research, the principal role of MeCP2 protein remains elusive. Is MeCP2 a regulator of genes, acting in concert with co-activators and co-repressors, predominantly as an activator of target genes or is it a methyl CpG binding protein acting globally to change the chromatin state and to supress transcription from repeat elements? If MeCP2 has no specific targets in the genome, what causes the differential expression of specific genes in the Mecp2 knockout mouse brain? We discuss the discrepancies in current data and propose a hypothesis to reconcile some differences in the two viewpoints. Since transcripts from repeat elements contribute to piRNA biogenesis, we propose that piRNA levels may be higher in the absence of MeCP2 and that increased piRNA levels may contribute to the mis-regulation of some genes seen in the Mecp2 knockout mouse brain. We provide preliminary data showing an increase in piRNAs in the Mecp2 knockout mouse cerebellum. Our investigation suggests that global piRNA levels may be elevated in the Mecp2 knockout mouse cerebellum and strongly supports further investigation of piRNAs in Rett syndrome.